Phosphor Plate
By optimizing the composition and particle size of (Y 1-x-y,Gd x,Ce y) 3Al 5O 12 and Al 2O 3, an efficient phosphor plate was prepared, which solved the problem of insufficient color difference and temperature characteristics in LED lighting, and achieved high brightness and uniform white light emission.
Patent Information
- Application Number
- JP2021162683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-28
- Filing Date
- 2021-10-01
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-10-01
AI Technical Summary
In the prior art, wavelength conversion members have problems of color differences and insufficient temperature characteristics in LED lighting, especially when the light conversion efficiency decreases under high temperature conditions, making it difficult to achieve uniform white light emission.
By controlling the composition ratio and particle size of (Y 1-x-y,Gd x,Ce y) 3Al 5O 12 and Al 2O 3, a phosphor with an average particle size of 4-6 μm was prepared, and the Gd/Ce ratio was 5.8-9.24 was ensured to ensure a YAG particle concentration of 20-30% and a porosity of less than 1.0%, forming a phosphor plate with a thickness of 150-250 μm.
The luminous flux is maintained at high temperatures, reducing color differences, improving light conversion efficiency and light uniformity, and ensuring high brightness white light emission.
Smart Images

Figure 0007628927000002 
Figure 0007628927000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphor plate for obtaining white light by wavelength conversion of light emitted from a light emitting diode (LED), and more particularly to a phosphor plate used for high-brightness white lighting. [Background technology]
[0002] LEDs are used in mobile phones and various display devices because of their power saving, long life, small size, etc. Furthermore, with the recent improvement in luminous efficiency, they have also attracted attention for lighting applications, and are rapidly becoming more widespread.
[0003] Currently, the mainstream method for white LED lighting is to obtain white light by mixing the light emitted by a blue LED with the light emitted from a phosphor that receives the incident blue light and emits yellow light, which is the complementary color of blue. Conventionally, wavelength conversion materials using such phosphors were generally made by dispersing phosphor powder in resin, but in recent years, composite materials with ceramics have been widely used from the viewpoint of heat resistance. However, in LED lighting, which requires a uniform emitted light color, wavelength conversion members made of the ceramic composite have the problem that they are prone to color unevenness.
[0004] In response to this, for example, Patent Document 1 discloses a method for producing a wavelength conversion member having high luminous intensity and high light conversion efficiency, the method including preparing a molded body containing an yttrium aluminum garnet phosphor having a composition represented by the following formula (I) and alumina particles having an alumina purity of 99.0 mass % or more, primarily firing the molded body to obtain a first sintered body, and secondary firing the first sintered body by hot isostatic pressing (HIP) treatment to obtain a second sintered body. (Y 1-a-b Gd a Ce b )3AlO 12 (I) (In formula (I), a and b are each 0≦a≦0.3 and 0 <b≦0.022である。)
[0005] Although the wavelength conversion member obtained by this manufacturing method is described as preferably having a Ce doping amount b in formula (I) exceeding 0 and being 0.022 or less (0 < b ≤ 0.022), in the examples, only b being 0.009 or less is exemplified. According to these, in order to obtain a desired fluorescence wavelength with Ce being 0.009 or less, it is necessary to dope a large amount of Gd, and when used in an LED light-emitting device, there is a problem that the wavelength conversion efficiency decreases as the temperature rises.
[0006] Further, Patent Document 1 describes that for the average particle diameters of the yttrium aluminum garnet-based phosphor and alumina particles in the stage of preparing the molded body, 1 μm or more and 50 μm or less and 0.2 μm or more and 1.3 μm or less are preferable, respectively, but the particle diameter of the sintered body after firing is not described, and it cannot be said that sufficient consideration has been given to issues such as maximizing the luminous efficiency of the yttrium aluminum garnet-based phosphor and chromaticity change, orientation characteristics, and in-plane uniformity (reduction of color unevenness) due to scattering of the sintered body by compounding alumina particles.
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0008] Heretofore, wavelength conversion members with high luminous intensity and high light conversion efficiency have been obtained, but further improvement has been required for chromaticity, orientation characteristics, and color unevenness. An object of the present invention is to provide a phosphor plate that emits white light with a large light flux amount, a small decrease in luminous efficiency even when the temperature rises, a small chromaticity difference, and suppressed in-plane unevenness.
Means for Solving the Problems
[0009] The phosphor plate of the present invention is 1-x-y ,Gd x ,Ce y )3AlO 12 and a sintered body of Al2O3 particles, wherein 0.07≦x≦0.11 and 0.010≦y≦0.015 are satisfied, and in the sintered body, the (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The average particle size of the particles is 4 μm or more and 6 μm or less, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 For a total of 100 vol% of the particles and Al2O3 particles, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The concentration of the Al2O3 particles is 20 vol% or more and 30 vol% or less, and the average particle size of the Al2O3 particles and the (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The ratio of the average particle size to the particle size Al2O3 / (Y 1-x-y ,Gd x ,Ce y )3AlO 12 is 1 or more and 2 or less, and the total thickness of the sintered body is 150 μm or more and 250 μm or less. The ratio (x / y) of Gd to Ce contained in the phosphor plate is preferably 5.8 or more and 9.24 or less. The porosity of the sintered body is preferably 1.0% or less. Effect of the Invention
[0010] According to the present invention, it is possible to provide a phosphor plate that has a large luminous flux, is suppressed from decreasing in luminous efficiency due to an increase in temperature, and emits white light with small chromaticity difference. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a schematic cross-sectional view of a fired body forming a phosphor plate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The phosphor plate of the present invention will now be described in detail. The phosphor plate of the present invention is 1-x-y ,Gd x ,Ce y )3AlO 12 and a sintered body of Al2O3 particles, wherein 0.07≦x≦0.11 and 0.010≦y≦0.015 are satisfied, and in the sintered body, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The average particle size of the particles is 4 μm or more and 6 μm or less, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 For a total of 100 vol% of the particles and Al2O3 particles, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The concentration of the Al2O3 particles is 20 vol% or more and 30 vol% or less, and the average particle size of the Al2O3 particles and the (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The ratio of the average particle size to the particle size Al2O3 / (Y 1-x-y ,Gd x ,Ce y )3AlO 12 is 1 or more and 2 or less, and the total thickness of the fired body is 150 μm or more and 250 μm or less.
[0013] In order to obtain the desired white light in an yttrium aluminum garnet (YAG) phosphor (hereinafter also referred to as "phosphor"), it is necessary to control the fluorescent wavelength by the amount of Gd and Ce doped. If a large amount of Gd is doped, the temperature characteristic of the phosphor decreases. The temperature characteristic refers to the temperature dependency of the wavelength conversion efficiency, and the decrease in temperature characteristic means that the wavelength conversion efficiency decreases as the temperature increases, which is a factor in the decrease in luminous flux when used at high temperatures. Since the wavelength conversion efficiency of a normal phosphor decreases as the temperature increases, there is a problem with the temperature characteristic. On the other hand, high temperature characteristic means that the decrease in wavelength conversion efficiency is small even when the temperature increases. In addition, the luminous flux is an index indicating the brightness of the white light obtained when a phosphor plate is mounted on a blue LED and white light is emitted.
[0014] On the other hand, if a large amount of Ce, a light-emitting element, is doped, the amount of light absorbed increases. For this reason, in order to transmit blue light, it is necessary to reduce the thickness and content of the phosphor. However, if the phosphor is too thin, the blue light cannot be sufficiently diffused within the phosphor, resulting in problems with chromaticity difference. Chromaticity difference is an index that represents the orientation characteristics of white light, and is the chromaticity difference (ΔCIE_x=CIE_x(60 degrees)-CIE_x(0 degrees)) of the straight light (0 degrees) and oblique light (60 degrees) of white light obtained when a phosphor plate is mounted on a blue LED and white light is emitted. To obtain high-brightness white light, it is preferable to have a small chromaticity difference (orientation characteristic). If the content of the phosphor is reduced too much, the luminous flux decreases due to absorption by the mixed materials such as alumina. On the other hand, excessive doping with Ce reduces the efficiency of conversion from blue light to yellow light due to concentration quenching, resulting in a decrease in luminous efficiency.
[0015] (Y 1-x-y ,Gd x ,Ce y )3AlO 12 In the case of YAG particles (hereinafter also referred to as "YAG particles"), there are optimum values for the doping amounts of Gd and Ce. 1-x-y ,Gd x ,Ce y )3AlO 12When part of the Y site of (Y) is replaced by Gd, the wavelength becomes longer, and when part of the Al site is replaced by Gd, the wavelength becomes shorter. 1-x-y ,Gd x ,Ce y )3AlO 12 When a part of the Y site of the compound is substituted with Ce, broad emission is observed due to the 5d-4f allowed transition. Based on these findings, the Gd content x and the Ce content y are 0.07≦x≦0.11 and 0.010≦y≦0.015, preferably 0.07≦x≦0.10 and 0.011≦y≦0.014. (Y 1-x-y ,Gd x ,Ce y )3AlO 12 In the particles, by setting x and y within the above-mentioned numerical range, it is possible to obtain white light emission with a large luminous flux, excellent temperature characteristics, and small chromaticity difference.
[0016] When x is less than 0.07, y must be greater than 0.015 to obtain the desired white light. When y exceeds 0.015, the luminous efficiency and luminous flux decrease. On the other hand, when x exceeds 0.11, y must be less than 0.010 to obtain the desired white light, and the temperature characteristics decrease.
[0017] The average particle size of the YAG particles in the fired body is 4 μm or more and 6 μm or less, preferably 4.4 μm or more and 5.6 μm or less. The average particle size is obtained by photographing the surface of the fired body using a field emission scanning electron microscope (FE-SEM), observing the reflected electron image, and measuring the particle size (in accordance with ISO13383-1:2012). Specifically, using the Hitachi High-Tech FE-SEM, a reflected electron image of the cross-sectional structure of the fired body is taken at 2000 times magnification, the maximum particle length of each of 200 particles observed in the image is measured, and the average value is calculated. When the average particle size is 4 μm or more and 6 μm or less, the YAG particles are uniformly dispersed in the fired body. When the YAG particles are uniformly dispersed, there are few voids in the phosphor plate, and high light conversion efficiency is obtained. If the average particle size is less than 4 μm, the crystallinity of the YAG particles, which are the phosphor component in the fired body, is low, resulting in a decrease in luminous efficiency and a decrease in luminous flux.If the average particle size exceeds 6 μm, blue light cannot be diffused sufficiently within the phosphor, the chromaticity difference (ΔCIE_x) increases, and the whiteness decreases.
[0018] In the fired body, the concentration of YAG particles is 20 vol% to 30 vol%, preferably 22 vol% to 26 vol%, relative to the total amount of YAG particles and Al2O3 particles (100 vol%). The concentration of YAG particles is determined by calculating the ratio of the YAG phase to the Al2O3 phase by XRD diffraction analysis of the phosphor plate. If the concentration of YAG particles is less than 20 vol%, the luminous flux decreases due to slight absorption in the Al2O3 layer. On the other hand, if it exceeds 30 vol%, scattering in the Al2O3 layer becomes insufficient, the chromaticity difference decreases, that is, the orientation characteristics deteriorate, and color unevenness occurs. Note that color unevenness indicates the chromaticity variation within the phosphor plate surface when a phosphor plate is mounted on a blue LED and white light is emitted, and the smaller this value, the more homogeneous white light is obtained.
[0019] Since the Al2O3 particles are a component other than the YAG particles that constitute the fired body, their concentration is 80 to 70 vol%, preferably 78 to 74 vol%, relative to the total amount of the YAG particles and the Al2O3 particles (100 vol%). The concentration of the Al2O3 particles can also be determined by XRD diffraction analysis of the phosphor plate.
[0020] The ratio of the average particle size of the Al2O3 particles to the average particle size of the YAG particles (average particle size of Al2O3 / average particle size of YAG) is equal to or greater than 1 and equal to 2. When the ratio is equal to or greater than 1 and equal to or less than 2, the phosphor plate becomes a highly efficient light-emitting element. However, when the ratio of the average particle size of Al2O3 / the average particle size of YAG is less than 1, that is, when the Al2O3 particles are smaller than the YAG particles on average, the luminous efficiency of the YAG particles is high, but the blue light and the fluorescent light are scattered excessively in the Al2O3 particles, so the extraction efficiency is reduced and the luminous flux is reduced. Also, when the ratio of the average particle size of Al2O3 / the average particle size of YAG is more than 2, that is, when the Al2O3 particles are larger than the YAG particles on average, the luminous efficiency of the phosphor plate is reduced and the luminous flux is reduced. Also, the wavelength-converted white light is emitted without being sufficiently diffused, so color unevenness occurs.
[0021] The method for producing the sintered body according to the present invention is not particularly limited. For example, Y2O3 (average particle size: 0.3 to 3 μm), CeO2 (average particle size: 0.1 to 1 μm), Gd2O3 (average particle size: 0.2 to 4 μm), and Al2O3 (average particle size: 0.2 to 10 μm) are used as raw materials, and the average particle sizes are appropriately specified. When a sintered body is produced, the raw materials are appropriately mixed so as to have a predetermined composition, and after molding and degreasing, the raw materials are mixed to obtain a sintered body having a particle size of 1.0 × 10 -2 A method of firing the phosphor plate in a vacuum atmosphere of about medium to low vacuum of less than Pa is used. A cross-sectional view of the fired body is shown in Fig. 1. As shown in Fig. 1, the phosphor plate of the present invention is a plate-like body having one main surface as a light incidence surface 2 and a light emission surface 3 as a main surface opposite to the light incidence surface 2.
[0022] The entrance surface 2 and the exit surface 3 are fired surfaces on which the YAG particles and Al2O3 particles are exposed without processing. "Non-processed" refers to the state in which the raw material powder is molded and fired as is, and no processing such as mechanical grinding or etching is performed after firing. If the entrance surface 2 and the exit surface 3 are processed by mechanical grinding or etching after firing to become so-called processed surfaces, the mechanical strength is low and cracks due to stress during mounting or use are likely to occur. In addition, defects that occur during processing may cause problems such as a decrease in luminous efficiency.
[0023] The arithmetic mean roughness (Ra) of the fired body that becomes the phosphor plate of the present invention over a measurement length of 4 mm is preferably 0.15 μm or more and 1.00 μm or less. This improves the light extraction efficiency and increases the luminous flux. The above Ra is measured in accordance with JIS B 0601:1994.
[0024] The total thickness of the fired body is 150 μm or more and 250 μm or less, preferably 180 μm or more and 230 μm or less. If the thickness is less than 150 μm, scattering is insufficient and the chromaticity difference is deteriorated. On the other hand, if the thickness exceeds 250 μm, scattering is large, the extraction efficiency is reduced, and the luminous flux is reduced. The extraction efficiency is the efficiency when blue light and yellow light are output from the phosphor plate, and the product of the luminous efficiency and the extraction efficiency is an index showing the performance of the phosphor.
[0025] The Gd / Ce ratio (x / y) in the fired body is preferably 4 to 15, more preferably 5.8 or more and 9.24 or less, and even more preferably 6.5 or more and 8.0 or less. When the Gd / Ce ratio (x / y) is less than 4, the Gd concentration is low, and there is a risk of emitting light at a shorter wavelength than the desired fluorescent wavelength. Or, the Ce concentration is high, and there is a risk of the luminous efficiency decreasing due to concentration quenching, and the luminous flux decreasing. On the other hand, when the Gd / Ce ratio (x / y) is more than 15, there is a risk of the temperature characteristics decreasing due to the high Gd concentration and the low Ce concentration. By setting the Gd / Ce ratio (x / y) in the fired body to 5.8 or more and 9.24 or less (more preferably, 6.5 or more and 8.0 or less), a more accurate fluorescent wavelength can be obtained, a decrease in luminous efficiency due to concentration quenching can be prevented, and a higher luminous flux can be obtained. Furthermore, the temperature characteristics can be improved.
[0026] The porosity of the fired body is preferably 1.0% or less. By setting the porosity to 1.0% or less, the phosphor plate can have high mechanical strength. In addition, it is possible to prevent the incident light from being excessively scattered, which increases the proportion of light returning to the incident surface 2 side and reduces the luminous efficiency. The porosity is measured in accordance with JIS R1634:1998. EXAMPLES
[0027] The present invention will be described in detail below based on examples, but the present invention is not limited to the examples shown below. [1] [(Y 1-x-y ,Gd x ,Ce y )3AlO 12 +Al2O3] sintered body Cerium oxide powder with an average particle size of 0.5 μm and a purity of 99.9%, yttrium oxide powder with an average particle size of 1.2 μm and a purity of 99.9%, gadolinium oxide powder with an average particle size of 0.9 μm and a purity of 99.9%, and aluminum oxide powder with an average particle size of 0.5 μm and a purity of 99.9% were mixed in a predetermined mixing ratio to obtain a raw material powder. By adjusting the particle sizes of the yttrium oxide powder, gadolinium oxide powder, cerium oxide powder, and aluminum oxide powder, the ((Y 1-x-y ,Gd x ,Ce y )3AlO 12 +Al2O3) in the fired body (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The average particle size of the Al2O3 particles was adjusted. 1-x-y ,Gd x ,Ce y )3AlO 12 When adjusting the average particle size of the particles, the particle sizes of the yttrium oxide powder, gadolinium oxide powder, and cerium oxide powder in the raw material powder were adjusted, and when adjusting the average particle size of the Al2O3 particles, the particle size of the aluminum oxide powder in the raw material powder was adjusted.
[0028] Ethanol, polyvinyl butyral (PVB) binder, and glycerin plasticizer were added to this raw material powder, and the mixture was ground and mixed for 40 hours in a ball mill using aluminum oxide balls to prepare a slurry.
[0029] This slurry was used to form a green sheet of a predetermined thickness by a doctor blade method. At this time, the total thickness of the phosphor plate was adjusted by adjusting the thickness of the green sheet. The obtained green sheet was degreased and calcined in the air, and then it was cut into 1.0×10 -2 The mixture was fired at 1700°C in a vacuum atmosphere of less than 100 Pa. 1-x-y ,Gd x ,Ce y )3AlO 12 +Al2O3) fired body was obtained. By appropriately adjusting the above conditions, samples of Examples 1 to 9 and Comparative Examples 1 to 14 shown in Table 1 were produced and evaluated as follows.
[0030] [2] [(Y 1-x-y ,Gd x ,Ce y )3AlO 12 +Al2O3] calcined body evaluation (Ce, Gd concentration) The Ce and Gd concentrations of the resulting phosphor plate were determined by ICP emission spectrometry. (Average particle size) The backscattered electron image of the surface of the phosphor plate was taken using a field emission scanning electron microscope (FE-SEM) to identify the YAG particles and Al2O3 particles. The average value of the maximum length of each particle was then taken as the average particle size (unit: μm). More than 200 YAG particles and Al2O3 particles were counted. ((Y 1-x-y ,Gd x ,Ce y )3AlO 12 (Percentage of The proportion of YAG particles was determined by calculating the ratio of the YAG phase to the Al2O3 phase through XRD diffraction analysis of the phosphor plate.
[0031] (Dominant Wavelength) The phosphor plate was cut into a size of 10 mm square, and placed in the center of a 4-inch integrating sphere. The integrating sphere was irradiated with excitation light, which was split into wavelengths of 450 nm±1 nm from a xenon lamp using a spectroscope. The emission spectrum of the phosphor plate was measured using a spectroscope (Ocean Insight's "Fiber Multichannel Spectrometer USB4000"), and the fluorescent dominant wavelength was calculated for the fluorescent component of 480 to 780 nm from the obtained emission spectrum.
[0032] (Temperature characteristics) The phosphor plate (10 mm x 10 mm) was placed in the center of a 4-inch integrating sphere equipped with a heater, and was irradiated with excitation light of 450 nm ± 1 nm in the same manner as in measuring the fluorescence wavelength, and the quantum efficiency at 25°C and 200°C was measured from the emission spectrum of the phosphor plate. The quantum efficiency at 200°C divided by the quantum efficiency at 25°C was taken as the temperature characteristic.
[0033] (luminous flux) The phosphor plate was processed to a size of 1 mm square and then fixed on a blue LED element (light-emitting area 1 mm square, light-emitting wavelength 450 nm) with silicone resin. The light emission was collected with a 4-inch integrating sphere, and the emission spectrum was measured with a spectrometer (Ocean Insight's "Fiber Multichannel Spectrometer USB4000"). The luminous flux was calculated from the obtained emission spectrum. The relative luminous flux was calculated by setting the luminous flux of a commercially available YAG:Ce phosphor (P46-Y3, manufactured by Kasei Optronics (now Mitsubishi Chemical Hi-Technica)) powder fixed at 22 vol% in commercially available phenyl silicone (OE-6630, manufactured by Dow Corning) resin on the same type of LED as 100.
[0034] (chromaticity difference) The phosphor plate was cut to a size of 1 mm square and then fixed on top of a blue LED element (light-emitting area 1 mm square, light-emitting wavelength 450 nm) with silicone resin. The chromaticity CIE_x of the light emitted from the phosphor plate was measured in the front direction (0 degrees) and oblique direction (60 degrees), and the value of CIE_x (60 degrees) - CIE_x (0 degrees) was taken as the chromaticity difference (ΔCIE_x). The smaller the chromaticity difference, the more excellent the orientation (orientation characteristics) of white light.
[0035] (Color unevenness) The phosphor plate was processed to a size of 1 mm square and then fixed on top of a blue LED element (light-emitting area 1 mm square, light-emitting wavelength 450 nm) with silicone resin. The color unevenness of the light-emitting surface of the phosphor plate was measured with a two-dimensional color luminance meter (Konica Minolta CA-2500), and the difference between the maximum and minimum values of CIE_x was taken as the color unevenness.
[0036] [Table 1]
[0037] From the above results, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 It was confirmed that by adjusting the particles so that 0.07≦x≦0.11 and 0.010≦y≦0.015, a phosphor plate excellent in orientation characteristics, luminous flux, and temperature characteristics can be obtained.
[0038] (Y 1-x-y ,Gd x ,Ce y )3AlO 12 It was confirmed that by adjusting the average particle size of the particles to 4 μm or more and 6 μm or less, a phosphor plate excellent in orientation characteristics and luminous flux can be obtained.
[0039] (Y 1-x-y ,Gd x ,Ce y )3AlO 12It was confirmed that by setting the particle concentration to 20 vol % or more and 30 vol % or less, a phosphor plate excellent in luminous flux, orientation characteristics and color unevenness can be obtained.
[0040] The average particle size of the Al2O3 particles and the (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The ratio of the average particle size of the particles Al2O3 / (Y 1-x-y ,Gd x ,Ce y )3AlO 12 It has been confirmed that by adjusting the value of the luminous flux to be between 1 and 2, a phosphor plate excellent in luminous flux and color uniformity can be obtained.
[0041] It was confirmed that by setting the total thickness of the fired body to 150 μm or more and 250 μm or less, a phosphor plate excellent in luminous flux and orientation characteristics can be obtained.
[0042] It was confirmed that by setting the Gd / Ce ratio (x / y) to be 5.8 or more and 9.24 or less, a phosphor plate excellent in luminous flux and temperature characteristics can be obtained. [Explanation of symbols]
[0043] 1. Fired body 2 Incidence plane 3. Exit surface 4. Aspects 5. Aspects
Claims
1. (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 Particles and Al 2 O 3 A phosphor plate made of a fired body of particles, 0.07≦x≦0.11 and 0.010≦y≦0.015; In the sintered body, (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 The average particle size of the particles is 4 μm or more and 6 μm or less, (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 Particles and Al 2 O 3 With respect to the total amount of particles being 100 vol%, (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 The particle concentration is 20 vol% or more and 30 vol% or less, The Al 2 O 3 The average particle size of the particles and the above (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 The ratio of the average particle size of the particles (Al 2 O 3 / (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 ) is 1 or more and 2 or less, A phosphor plate characterized in that the fired body has a total thickness of 150 μm or more and 250 μm or less.
2. 2. The phosphor plate according to claim 1, wherein the Gd / Ce content ratio (x / y) in the phosphor plate is 5.8 or more and 9.24 or less.
3. 3. The phosphor plate according to claim 1, wherein the sintered body has a porosity of 1.0% or less.
Citation Information
Patent Citations
Composite ceramic fluophor for high-power laser illumination, preparation method of composite ceramic fluophor and light source device
CN109896857A
Wavelength-conversion laminated composite, and method for manufacturing wavelength-conversion laminate
JP2016018878A
Wavelength conversion sintered body
JP2016138034A
Fluophor and light-emitting device
JP2017149847A
Method of manufacturing wave length conversion member
JP2018172628A